LIABILITY FOR ADMINISTRATIVE DEFENSE IN THE FIELD OF CIVIL AVIATION - Слободська, Ірина Андріївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2018)
The purpose: of the article is to fill the gaps in the current legislation of Ukraine in the field of civil aviation, namely: it is proposed to consider a legal entity as a subject of administrative liability in the field of civil aviation of Ukraine, as well as to introduce into the current legislation of Ukraine the term «administrative offenses in the field of civil aviation». Methods used: a) at the empirical level of research: systemic, synthetic, abstraction, deduction; b) on the theoretical level of research: systemic; c) specific scientific methods of legal research: the study of scientific works of famous scientists, who applied general scientific methodology for studying a specific branch of science; the analysis of scientific papers by leading scientists, who, simultaneously with the general problems of their industry, studied the issues of this branch; generalization of ideas of scientists who directly studied this problem; analysis of the concepts in this area of scientific and practical activity of Ukrainian scientists and practitioners. Results: it is concluded that an administrative offense in the field of civil aviation can be defined as an unlawful, guilty (intentional or negligent) act or omission that infringes on the established procedure of management, activity in the field of civil aviation and violates the rights of subjects of aviation activity, others individuals and legal entities.